2020
DOI: 10.1039/c9cs00840c
|View full text |Cite
|
Sign up to set email alerts
|

The use of yttrium in medical imaging and therapy: historical background and future perspectives

Abstract: Yttrium presents a wide palette of isotopes with interesting coordination and radiochemical properties. We review its most prominent isotopes and their diverse medical uses in therapy and imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…To evaluate the protein-based radioisotope purification strategy, we first attempted to recover 90 Y 3+ from 90 Sr 2+ sources using LanM. 90 Y 3+ is used for radioimmunotherapy and medical imaging (e.g., SPECT/CT, gamma, and PET) ( 31 , 32 ). 90 Sr 2+ has a long half-life (28.9 years) and β-decays to 90 Y 3+ (2.66 days).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the protein-based radioisotope purification strategy, we first attempted to recover 90 Y 3+ from 90 Sr 2+ sources using LanM. 90 Y 3+ is used for radioimmunotherapy and medical imaging (e.g., SPECT/CT, gamma, and PET) ( 31 , 32 ). 90 Sr 2+ has a long half-life (28.9 years) and β-decays to 90 Y 3+ (2.66 days).…”
Section: Resultsmentioning
confidence: 99%
“…The pure beta emitter Yttrium-90 (E βmax = 2.28 MeV, t 1/2 = 64 h) is a radionuclide of choice, that has found wide use for internal radiotherapy [50]. Thus, numerous studies have demonstrated its therapeutic efficacy and safety [21,51]. Among its prominent applications is transarterial radioembolization for the treatment of primary and secondary liver cancers [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of gamma emission is beneficia in terms of radioprotection constraints [20]. Besides its already mentioned use in micro spheres for radioembolization, it has been used in peptide receptor radionuclide therapy (PRRT) and radioimmunotherapy (RIT) of various tumor types [21]. 90 Y-labeling of Lip iodol has also been described [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of nanotechnology and nanomedicine, nanoradiosensitizers, such as gold, platinum, superparamagnetic iron oxides, quantum dots, rare-earth nanomaterials, etc., have recently drawn tremendous attention for solid tumor treatment. Among them, gold nanoparticles are considered extremely promising CT imaging and radiotherapeutic agents in biomedical applications due to their morphology/size controllability, strong X-ray absorption coefficient, excellent biocompatibility, and high therapeutic efficacy. To date, many approaches have been reported to improve the radiotherapeutic efficacy of solid tumors by enhancing the tumor specificity and targeting capability of AuNPs through the decoration of certain tumor-targeting moieties (e.g., small molecules, peptides, antibodies, etc. ) onto the surface.…”
Section: Introductionmentioning
confidence: 99%